The evolution of technological substitution in low-wage labor markets - Daniel Aaronson; Brian J. Phelan (Federal Reserve Bank of Chicago, 2020)
This paper uses minimum wage hikes to evaluate the susceptibility of low-wage employment to technological substitution. We find that automation is accelerating and supplanting a broader set of low-wage routine jobs in the decade since the Financial Crisis. Simultaneously, low-wage interpersonal jobs are increasing and offsetting routine job loss. However, interpersonal job growth does not appear to be enough - as it was previous to the Financial Crisis - to fully offset the negative effects of automation on low-wage routine jobs. Employment losses are most evident among minority workers who experience outsized losses at routine-intensive jobs and smaller gains at interpersonal jobs.
Keywords: J15; J21; J24; J38; O33; 330; Low-wage automation; routine-biased technical change; minimum wage